Spontaneous Resolution of Bilateral Central Serous Chorioretinopathy Following Conservative Management: A Case Report - Ramzi Amin; Muhammad Fahmi (HM Publisher, 2025)
Central serous chorioretinopathy (CSCR) is characterized by serous detachment of the neurosensory retina, often associated with dysfunction of the retinal pigment epithelium (RPE) and choroidal hyperpermeability. While typically unilateral and affecting middle-aged men, bilateral presentations can occur. Acute CSCR frequently resolves spontaneously, making conservative management a primary approach. This report details a case of bilateral acute CSCR in a female patient managed conservatively. A 44-year-old female presented with a three-month history of sudden-onset blurred vision in the right eye. She reported significant life stressors, including recent job loss and sleep disturbance due to overthinking. Best-corrected visual acuity (BCVA) was 6/6 in both eyes. Fundus examination revealed subtle macular elevation bilaterally. Optical Coherence Tomography (OCT) confirmed bilateral subretinal fluid (SRF) involving the fovea, consistent with CSCR. Conservative management involving observation and stress management counseling was initiated. Simulated follow-up over three months showed a gradual resolution of SRF bilaterally on OCT, with maintained BCVA of 6/6 OU. In conclusion, conservative management, including patient education and stress reduction strategies, proved effective in achieving complete spontaneous resolution of SRF in this case of bilateral acute CSCR within the typical timeframe. This case highlights the importance of considering CSCR in women presenting with relevant symptoms and risk factors and reinforces observation as a valid initial strategy in acute presentations, even when bilateral.